Dietary advanced glycation end-products and their associations with body weight on a Mediterranean diet and low-fat vegan diet: a randomized, cross-over trial - Kahleova, Hana; Znayenko-Miller, Tatiana; Motoa, Giulianna; Eng, Emma; Prevost, Alex; Uribarri, Jaime; Holubkov, Richard; Barnard, Neal D. (Frontiers in Nutrition, 2024)
Objecve: Evidence suggests that changes in dietary advanced glycaon end-products (AGEs) may influence body weight, but the effects of different dietary paterns remain to be explored.The aim of this study was to compare the effects of a Mediterranean and a low-fat vegan diet on dietary AGEs and test their associaon with body weight.In this randomized cross-over trial, 62 overweight adults were assigned to a Mediterranean or a low-fat vegan diet for 16-week periods in random order, separated by a 4-week washout. Body weight was the primary outcome. Three-day diet records were analyzed using the Nutrion Data System for Research soware and dietary AGEs were esmated, using an established database. Stascal approaches appropriate for crossover trials were implemented.Results: Dietary AGEs decreased by 73%, that is, by 9,413 kilounits AGE/day (95% -10,869 to -7,957); p<0.001, compared with no change on the Mediterranean diet (treatment effect -10,303 kilounits AGE/day [95% CI -13,090 to -7,516]; p<0.001). The parcipants lost 6.0 kg on average on the vegan diet, compared with no change on the Mediterranean diet (treatment effect -6.0 kg [95% CI -7.5 to -4.5]; p<0.001). Changes in dietary AGEs correlated with changes in body weight (r=+0.47; p<0.001) and remained significant aer adjustment for total energy intake (r=+0.39; p=0.003).Conclusions: Dietary AGEs did not change on the Mediterranean diet but decreased on a lowfat vegan diet, and this decrease was associated with changes in body weight, independent of energy intake.